Archeal lectins: An identification through a genomic search. Issue 1 (16th November 2015) - Abhinav, K. V.; Samuel, Ebenezer; Vijayan, M.
ABSTRACT: Forty‐six lectin domains which have homologues among well established eukaryotic and bacterial lectins of known three‐dimensional structure, have been identified through a search of 165 archeal genomes using a multipronged approach involving domain recognition, sequence search and analysis of binding sites. Twenty‐one of them have the 7‐bladed β‐propeller lectin fold while 16 have the β‐trefoil fold and 7 the legume lectin fold. The remainder assumes the C‐type lectin, the β‐prism I and the tachylectin folds. Acceptable models of almost all of them could be generated using the appropriate lectins of known three‐dimensional structure as templates, with binding sites at one or more expected locations. The work represents the first comprehensive bioinformatic study of archeal lectins. The presence of lectins with the same fold in all domains of life indicates their ancient origin well before the divergence of the three branches. Further work is necessary to identify archeal lectins which have no homologues among eukaryotic and bacterial species. Proteins 2016; 84:21–30. © 2015 Wiley Periodicals, Inc.